Sentido de comunidade, lazer e pobreza: o impacto da Areninha do Conjunto Palmeiras, Fortaleza/CE - Ramos, Tássia Oliveira (2022)
This work has as general objective to analyze the leisure habits in Areninha of the Conjunto Palmeiras neighborhood to strengthen the sense of community of the residents. The Sense of Community has been fundamental in studies and interventions of Community Psychology, as it presents characteristics of community bonds that can contribute to the struggle for community rights in search of well-being. Areninha is a public facility consisting of a synthetic turf soccer field and is surrounded by a children's playground and an outdoor gym. This type of equipment was initially built in neighborhoods in the city of Fortaleza that have a high rate of social vulnerability and a low Human Development Index. The present work had as a starting question how does this sports equipment affect the lives of the residents of its surroundings? This study had a qualitative methodology, carrying out three semi-structured interviews, one of them in pairs and therefore had the participation of four residents of the Conjunto Palmeiras neighborhood. Content analysis was carried out, from the categorical analysis in order to a thematic categorization centered on the dimensions of the categories poverty, Sense of Community and leisure habits. It was also possible to conceive inductive categories from the interviewees' statements. Data were organized using atlas.ti software and categories were listed in macrocategories or related to each other. Regarding the understanding of poverty, the facts of the subjects not having enough to eat, living in unsanitary conditions without basic sanitation or not having acess to rights for not having a registration document at the registry office were evidenced as concrete aspects. The psychosocial aspects of fatalism in the face of the imposed situation, of conformist attitudes that can generate stigmatization and the shame of being in this condition were also perceptible. As for the Sense of Community, social participation stands out as a deeply related factor, since it is considered a protective factor for the community and/or vulnerability. Through participation in leisure or sports activities, people in the community got to know each other better, thus feeling more united. Engagement in social struggles is another characteristic that appeared in the speeches about the community. We seek do understand leisure practices in communities that live in multidimensional poverty and we affirm that, with the presence of leisure equipment, more public policies to support equipment need to be provided - such as those that favor community strengthening, with more access to commerce and to security. In addition, specificities of public policies for sport and leisure are necessary, bringing professionals in the area of ​​sports and physical activity to carry out sports initiation for people of different ages and genders and, thus, guarantee access to leisure for everyone in the community. In this sense, we think about the efficiency of a public policy that promotes the practice of quality physical and sports activity and that brings other policies, so that there is an expanded discussion of Public Policies for Sport and Leisure from the impressions of the impact of the Areninha in a peripheral community.